Trusting trade and the private sector for food security in Southeast Asia [ - Alavi, Hamid; Htenas, Aira (Directions in development. Trade, 2012)
Trusting Trade and the Private Sector for Food Security in Southeast Asia challenges policymakers who oversee the rice sector in Southeast Asia and reexamines deep-rooted preceptsabout their responsibilities. The authors argue that fixating on national self-sufficiency hasbeen costly and counterproductive, and cooperation can both improve rice productionat home and expand regional trade. Trusting Trade specifically examines private sectorparticipation in the rice and (yellow) maize markets in five countries in the Association ofSoutheast Asian Nations (ASEAN)-Indonesia, Malaysia, the Philippine